The Effect of Return on Asset (ROA), Quick Ratio (QR), and Size on Stock Return of Metal and Material Companies in the 2014-2020 Period - Wijaya, John Henry; Dwisandi, Dea Nova; Wigelar, Giusti Rifan; Lanteng, Ryandi Fahmi; Abdurahman, Moh Irsyad; Kamilah, Bintan; Saudi, Mohd Haizam (CENTRAL ASIA AND THE CAUCASUS, 2022)
Return on investment depends on firm’s permormance which is evaluated from its stock performance. This study aims to analyze the effect of Return on Assets (ROA), Quick Ratio (QR), and Firm Size on stock returns. The object chosen in this study is basic material manufacturing firms listed on the Indonesia Stock Exchange in the 2014-2020 period. 14 Metals and Materials sub-sector firms were selected as samples. The analysis technique used in this study is by using software program E-views 9. The results of the research from the data obtained indicate that Return On Assets (ROA), Quick Ratio (QR), and Firm Size have an effect on to stock returns. The Quick Ratio (QR) and Firm Size have positive correlation on stock returns. However, Return on Asset (ROA) variable has an anomaly effect on stock returns, when Return on Asset (ROA) decreases it will increases the value of stock returns.